TAKSONOMI GULMA PADI (Oryza sativa) DI AREAL PERSAWAHAN JAKABARING PALEMBANG - Dewi Rosanti (Universitas PGRI Palembang, 2016)
ABSTRACT Taxonomic studies weeds of rice (Oryza sativa) in paddy fields Jakabaring Palembang was held in September to October 2015, the descriptive survey method. Sampling is done in a systematic way. Weeds found on land rice plant (Oryza sativa) consists of 1 divisio, 2 class, 7 order, 7 of family, genus and 12 species. All weeds are divisio Spermatophyta, which can be divided into class Dicotyledoneae. Family of Class Dicotyledoneae is Asteraceae as species Ageratum conyzoides (bandotan) and Crassocephalum crepidioides (sintrong); familia Convolvulaceae as species Ipomoea aquatica (water spinach); familia Euphorbiaceae as Acalypha indica (kucingan), Phyllanthus niruri (meniran) and Euphobia hirta (patikan kebo); familia Fabaceae as species Mimosa pudica var unijuja (shy daughter). Familia of class Monocotyledoneae are familia Cyperaceae as species Cyperus compressus (puzzle), Cyperus pilosus (puzzles) and Ischaemum timorens (jakut racket); familia Hydrocharitaceae as Blyxa echinosperma (junjung water); familia Poaceae as Digittaria longiflora (grass digataria). Keywords: weed, Oryza sativa, rice fields, taxonomy ABSTRAK Penelitian taksonomi gulma padi (Oryza sativa) di areal persawahan Jakabaring Palembang telah dilaksanakan pada bulan September sampai dengan bulan Oktober 2015, menggunakan metode survey deskriptif. Gulma yang terdapat pada lahan tanaman padi (Oryza sativa ) terdiri dari 1 divisio, 2 class, 7 ordo, 7 familia, genus dan 12 spesies. Semua gulma merupakan divisio Spermatophyta, yang dapat dibedakan menjadi class dicotyledonae. Familia dari Class Dicotyledoneae yaitu Asteraceae dengan spesies gulma Ageratum conyzoides (bandotan) dan Crassocephalum crepidioides (sintrong); familia Convolvulaceae dengan spesies Ipomoea aquatica (kangkung air); familia Euphorbiaceae dengan spesies Acalypha indica (kucingan), Phyllanthus niruri (meniran) dan Euphobia hirta (patikan kebo); familia Fabaceae dengan spesies Mimosa pudica var unijuja (putri malu). Familia dari class Monocotyledoneae yaitu familia Cyperaceae dengan spesies Cyperus compressus (teki), Cyperus pilosus (teki) dan Ischaemum timorens (jakut raket); familia Hydrocharitaceae dengan spesies Blyxa echinosperma (junjung air); familia Poaceae dengan jenis Digittaria longiflora (rumput digataria). Kata Kunci : Gulma, Oryza sativa, sawah, taksonomi